2013
DOI: 10.1002/jor.22511
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic healing response of the human anterior cruciate ligament: An histological study of reattached ACL remnants

Abstract: A reattachment of the tibial remnant of the torn anterior cruciate ligament (ACL) to the posterior cruciate ligament is sometimes observed during surgery and apparently implies that the human ACL does have a healing response. The aim of this study was to investigate whether this reattachment tissue has similar histological characteristics of a healing response as the medial collateral ligament (MCL), which can heal spontaneously. Standard histology and immunostaining of a-smooth muscle actin and collagen type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 32 publications
0
90
0
Order By: Relevance
“…As supported by Nguyen et al, 13 proximal avulsion tears behave differently than midsubstance ACL tears. On the basis of the findings by Sherman et al, 8 proximal avulsion tears with high tissue quality yielded the highest probability of successful results.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…As supported by Nguyen et al, 13 proximal avulsion tears behave differently than midsubstance ACL tears. On the basis of the findings by Sherman et al, 8 proximal avulsion tears with high tissue quality yielded the highest probability of successful results.…”
Section: Discussionmentioning
confidence: 67%
“…Nguyen et al 13 investigated the intrinsic healing response of the ACL with histologic characteristics of the medial collateral ligament (MCL). They concluded that the histologic features of the proximal third of the ACL and the MCL were similar and a similar healing response can be expected.…”
mentioning
confidence: 99%
“…Uniform gel contraction of the stress-free gels also resulted in cells with a stellate like cell morphology with disorganized fiber organization that resembles early scar tissue. 34 Gel contraction may increase the number of cell-cell contacts, 2 and could play a role in modulating the different cellular responses observed between the three static stress conditions (Table 1). 3 …”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of the reasons for the failure of ACL to spontaneously heal will help us develop newer treatment methods. Although we are still unaware of the entire mechanism, and the signaling pathways involved in ACL spontaneous healing, recent studies have identified few probable candidates that may be possible key players [41,[47][48][49][50]. Some studies have reported that injured ACL has the same functional healing response as other extra-articular ligaments in terms of cellularity and vascularity.…”
Section: Discussionmentioning
confidence: 99%